The expanding impact of T-regs in the skin - Hajam, Edries Yousaf; Panikulam, Patricia; Chu, Chung-Ching; Jayaprakash, Haarshadri; Majumdar, Amitabha; Jamora, Colin (Frontiers in Immunology, 2022)
As the interface between the body and the environment, the skin functions as the physical barrier against external pathogens and toxic agents. In addition, the skin is an immunologically active organ with a plethora of resident adaptive and innate immune cells, as well as effector molecules that provide another layer of protection in the form of an immune barrier. A major subpopulation of these immune cells are the Foxp3 expressing CD4 T cells or regulatory T cells (T-regs). The canonical function of T-regs is to keep other immune cells in check during homeostasis or to dissipate a robust inflammatory response following pathogen clearance or wound healing. Interestingly, recent data has uncovered unconventional roles that vary between different tissues and we will highlight the emerging non-lymphoid functions of cutaneous T-regs. In light of the novel functions of other immune cells that are routinely being discovered in the skin, their regulation by T-regs implies that T-regs have executive control over a broad swath of biological activities in both homeostasis and disease. The blossoming list of non-inflammatory functions, whether direct or indirect, suggests that the role of T-regs in a regenerative organ such as the skin will be a field ripe for discovery for decades to come.